Food industry and packaging materials performance-oriented guidelines for users - Parisi, Salvatore (Smithers Rapra Technology Ltd., 2013)
This book provides detailed and comprehensible information about Quality Control (QC) in the industry. Different viewpoints are explained in relation to food companies, packaging producers and technical experts, including regulatory aspects. One of the most important steps is the comprehension of QC failures in relation to the 'food product' (food/packaging). The book also presents a detailed selection of proposals about new testing methods. On the basis of regulatory obligations in the EU about the technological suitability of food packaging materials, a list of 'performance-oriented' guideli.
Keywords: Food -- Packaging -- Quality control.; Food industry and trade -- Quality control.; elektronické knihy; electronic books